2013
DOI: 10.1037/a0033075
|View full text |Cite
|
Sign up to set email alerts
|

A grounded theory exploration of undergraduate experiences of vicarious unemployment.

Abstract: The experiences of vicarious unemployment (VU) among 17 undergraduate student participants who had a primary caregiver who was involuntarily unemployed were explored using grounded theory (Charmaz, 2006; Glaser & Strauss, 1967). Data from semistructured interviews with 15 women and 2 men revealed the nuanced nature of experiences with unemployment among those who experience it vicariously. Struggles related to increased family stress and experiences with stigma were common across participants. As participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 60 publications
1
21
0
Order By: Relevance
“…These results also extend those from previous research (e.g., Gutman & Eccles, 1999;Simons et al, 1991;Ullah, 1990) that documented the detrimental effects of financial strain on adolescent development in other domains (e.g., academic achievement, psychological health, and commitment to obtaining employment). The negative relationship between heightened levels of financial stress and strain and work hope also offers quantitative support for Thompson, Nitzarim, Her, and Dahling's (2013) grounded theory investigation of the experience of vicarious unemployment among college students, which highlighted the implications of caregiver unemployment on college students' perceived levels of stress related to their own educational and vocational development.…”
Section: Discussionmentioning
confidence: 77%
“…These results also extend those from previous research (e.g., Gutman & Eccles, 1999;Simons et al, 1991;Ullah, 1990) that documented the detrimental effects of financial strain on adolescent development in other domains (e.g., academic achievement, psychological health, and commitment to obtaining employment). The negative relationship between heightened levels of financial stress and strain and work hope also offers quantitative support for Thompson, Nitzarim, Her, and Dahling's (2013) grounded theory investigation of the experience of vicarious unemployment among college students, which highlighted the implications of caregiver unemployment on college students' perceived levels of stress related to their own educational and vocational development.…”
Section: Discussionmentioning
confidence: 77%
“…Loss of a job often means loss of medical insurance, which will only exacerbate financial pressure, particularly for families that had a low income. Many previous studies have shown that poverty or unemployment is significantly associated with increased family stress (e.g., Howe et al, 2012;Pignault & Houssemand, 2018;Thompson et al, 2013).…”
Section: Stressors Associated With Covid-19mentioning
confidence: 99%
“…Students who require funding often hail from marginalised groups. Although one cannot homogenise such groups, they face many obstacles: family stresses, financial strain, stigmatisation, social integration, and lack of access to the culture of the academy (Thompson et al, 2013). That said, such challenges are not only felt by so-called "disadvantaged" students.…”
Section: Student Funding: Challenges and Debatesmentioning
confidence: 99%